2015
DOI: 10.1080/15384101.2015.1021519
|View full text |Cite
|
Sign up to set email alerts
|

Stranglehold on the spindle assembly checkpoint: the human papillomavirus E2 protein provokes BUBR1-dependent aneuploidy

Abstract: The Human Papillomavirus (HPV) E2 protein, which inhibits the E6 and E7 viral oncogenes, is believed to have anti-oncogenic properties. Here, we challenge this view and show that HPV-18 E2 over-activates the Spindle Assembly Checkpoint (SAC) and induces DNA breaks in mitosis followed by aneuploidy. This phenotype is associated with interaction of E2 with the Mitotic Checkpoint Complex (MCC) proteins Cdc20, MAD2 and BUBR1. While BUBR1 silencing rescues the mitotic phenotype induced by E2, p53 silencing or prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…We previously identified a potential mechanism by which E2 could induce cell cycle mitotic arrest in vitro ; E2 protein inactivates the mitotic ubiquitin ligase APC/C and supports the accumulation of mitotic regulators such as CyclinB1 [ 13 ]. Furthermore, E2 can interact with elements of the spindle assembly checkpoint to delay its inactivation during mitosis, thus inducing the mitotic arrest described here and in previous reports [ 13 , 14 ]. In the current report, we demonstrate that the activation of host cell DDR signal by HPV16-E2 occurs concomitantly with M-phase entry and is maintained during the prolonged E2-induced prophase arrest in vitro .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We previously identified a potential mechanism by which E2 could induce cell cycle mitotic arrest in vitro ; E2 protein inactivates the mitotic ubiquitin ligase APC/C and supports the accumulation of mitotic regulators such as CyclinB1 [ 13 ]. Furthermore, E2 can interact with elements of the spindle assembly checkpoint to delay its inactivation during mitosis, thus inducing the mitotic arrest described here and in previous reports [ 13 , 14 ]. In the current report, we demonstrate that the activation of host cell DDR signal by HPV16-E2 occurs concomitantly with M-phase entry and is maintained during the prolonged E2-induced prophase arrest in vitro .…”
Section: Discussionsupporting
confidence: 60%
“…We hypothesized that HPV-E2 protein might also be involved in initiating the DNA damage response as it is part of the viral DNA replication process and is expressed in precursors of cancer. E2 from the high risk HPV16 and HPV18 types can directly induce cell cycle arrest during mitosis and lead to genomic instability [ 13 , 14 ]. Recent reports have also linked normal mitotic entry of non-infected cell with the induction of a DDR signal [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that the human papillomavirus (HPV) E2 protein interacts with the MCC and over-activates the SAC, resulting in abnormal mitosis followed by aneuploidy [83].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is facilitated by activation of the spindle assembly checkpoint through interaction with mitotic checkpoint proteins BubR1, Mad2 and Cdc20 during metaphase, which in turn prevents the activation of the anaphase‐promoting complex required for progression to anaphase . Because prolonged activation of the spindle assembly checkpoint is known to result in chromosomal missegregation and genomic instability, it is no surprise that overexpression of HPV18 E2 results in aneuploidy and in the induction of DNA breaks of the host chromosomes . How much this phenotype contributes to cancerous progression during in vivo infection remains speculative at this point and needs further exploration.…”
Section: Consequences Of Tetheringmentioning
confidence: 99%